Chiral selectivity of polyglycerol‐based amphiphiles incorporating different aromatic cores (Phys. Status Solidi B 11/2015). Issue 11 (6th November 2015) - Setaro, A.; Popeney, C. S.; Witt, M. U.; Bluemmel, P.; Glaeske, M.; Haag, R.; Reich, S.
Abstract : Isolation of single chiral species is the biggest technological challenge towards the extensive technological implementation of single walled carbon nanotubes. Directed growth of a single chiral species has been achieved but only yields a limited number of different species. Other techniques based on the different density or mobility of different tubes, such as density gradient ultracentrifugation, gel dielectrophoresis, efficiently separate different targeted tubes species at the cost of high material loss. Liquid phase separation, on the other hand, is an easily up‐scalable, one‐step technique with high separation yield. Taking advantage of the spontaneous separation between two immiscible phases, effective separation between metallic and semiconducting tubes based on their suspension with different surfactants is achieved. Setaro et al. (pp. 2536–2540 ) present a set of novel amphiphiles sharing the same head and tail but comprising different cores to target and extract specific tube chiralities. This can be exploited to set up a database of specific molecules for the isolation of targeted nanotube species.